Incidence of hyponatremia and its utility as an indicator of morbidity in children hospitalised with community acquired pneumonia - Natarajan, Thrilok; Sahubar Sadique, Thahsheen Nilofar; Shanmugham, Kabilan (International Journal of Contemporary Pediatrics, 2020)
Background: The aims of the study were to determine the incidence of hyponatremia associated with pneumonia and to assess its utility as an indicator of morbidity in children hospitalized with community acquired pneumonia between 2 months and 5 years of age. Methods: This was a prospective study of children aged 2 months to 5 years hospitalized with community acquired pneumonia. 120 children aged 2 months to 5 years with symptoms of lower respiratory tract infection and had radiological evidence of pneumonia were recruited into the study. Children with chronic diseases, previously treated with intravenous fluids and those with chronic drug intake were excluded from study. Results: Of the 120 children, 40.8% (49/120) had hyponatremia at admission. The relationship of hyponatremia to different clinical and laboratory parameters was analyzed. Sixty-one percent (31/51) of children under 1 year and 26% (18/69) of children between 1 to 5 years of age had hyponatremia (p=0.001). Hyponatremia was seen more commonly in children with severe pneumonia, with initial high temperature(p=0.001), with tachycardia (p=0.001), leukocytosis (p=0.001), increased neutrophils (p=0.001) and reactive thrombocytosis (p<0.001) and in children who had hemodynamic instability on admission (p<0.001). All 11(9.2%) children who required mechanical ventilation had hyponatremia (p<0.001). Consolidation was significantly associated with hyponatremia (p<0.001). Hyponatremia also showed a significant association with prolonged hospital stay (p<0.001). Conclusion: The incidence of hyponatremia in children hospitalised with pneumonia is 40.8%. This study concludes that the hyponatremia shows a significant association with the morbidity of the disease like requirement of intensive care and mechanical ventilation, hemodynamic instability and prolonged hospital stay. Hence the presence of hyponatremia at admission can be used as an indicator of morbidity.